Pengaruh Harga Dan Pelayanan Terhadap Kepuasan Penumpang Transportasi Darat KA Sibinuang Jurusan Padang-Pariaman - Ronny Mardhino; Yulhendri Yulhendri (Jurnal Ecogen, 2019)
This study aims to reveal the effect of price and service on consumer satisfaction of Sibinuang railroad transportation in Padang-Pariaman. This study departs from the phenomena associated with passenger dissatisfaction with Sibinuang train services. This research is a type of causative. Causative research aims to analyze the relationship between one variable with another variable or how a variable affects other variables. In this case the effect of price and service on the satisfaction of the passengers of the Sibinuang Train PT. Kereta Api Indonesia (Persero) Regional Division II West Sumatera. The population in this study are people who have used the Sibinuang train service majoring in Padang-Pariaman, PT. Kereta Api Indonesia (Persero) Regional Division II West Sumatera. The data used are primary data obtained through observation, interviews, questionnaires or questionnaires distributed at several stations / shelters that are passed by the train and secondary data obtained from the company. The sampling technique used in this study is a non-probability sampling method with accidental sampling technique .. The analytical method used is multiple regression analysis using SPSS version 21. For hypothesis testing using the F test and the statistical test t with a level of α = 0.05 . The results of this study indicate that 1) the price does not significantly influence the satisfaction of Sibinuang Train passengers PT. Kereta Api Indonesia (Persero) Regional Division II West Sumatera. 2) Service has a significant effect on the satisfaction of Sibinuang Railroad passengers of PT. Kereta Api Indonesia (Persero) Regional Division II West Sumatera.Keywords: price, service, and passenger satisfaction.